2018
DOI: 10.48550/arxiv.1810.09865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bounds on spectral norms and barcodes

Asaf Kislev,
Egor Shelukhin

Abstract: We investigate the relations between algebraic structures, spectral invariants, and persistence modules, in the context of monotone Lagrangian Floer homology with Hamiltonian term. Firstly, we use the newly introduced method of filtered continuation elements to prove that the Lagrangian spectral norm controls the barcode of the Hamiltonian perturbation of the Lagrangian submanifold, up to shift, in the bottleneck distance. Moreover, we show that it satisfies Chekanov type low-energy intersection phenomena, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 97 publications
3
45
0
Order By: Relevance
“…The same is true of the spectral norm γ and its variant γ ext on L L 0 (M ). This follows from the proof of Theorem E in [KS18]. When M = T * L 0 , and γ is extended to L e (T * L 0 ) ∩ L m(1,0) (T * L 0 ), the same stay true.…”
Section: Iia J-adapted Metricsmentioning
confidence: 58%
See 2 more Smart Citations
“…The same is true of the spectral norm γ and its variant γ ext on L L 0 (M ). This follows from the proof of Theorem E in [KS18]. When M = T * L 0 , and γ is extended to L e (T * L 0 ) ∩ L m(1,0) (T * L 0 ), the same stay true.…”
Section: Iia J-adapted Metricsmentioning
confidence: 58%
“…(d F = γ ext ): This is a variant of the usual spectral norm, as defined in [KS18], where it is also shown that it is a metric. We also have that L (M ) ⊆ L L 0 (M ) and F = F = ∅, but we only ask that L 0 ∈ L we (M ).…”
Section: J-adapted Metrics On Collections Of Lagrangian Submanifoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistence method has been widely applied to symplectic and contact geometry. After the pioneering work by Polterovich-Shelukhin [PS16], persistence modules have been used for the study of barcodes of Floer cohomology complexes in Usher-Zhang [UZ16] and the study of spectral norms in Kislev-Shelukhin [KS18b], to name a few. In this paper, we also investigate the relation between the interleaving-like distance d D(M ) and the spectral norm (see Theorem 5.8).…”
Section: Related Workmentioning
confidence: 99%
“…One direction of investigation to better understand d Hofer is to investigate how dynamical properties of Hamiltonian diffeomorphisms vary under perturbations with respect to d Hofer . This has been pursued by several authors, see [16,36,43,44,46]. Floer homology together with its action filtration behaves in a very stable way under perturbations with respect to d Hofer .…”
mentioning
confidence: 99%